Characterization and behaviour of fluoride-containing semiconductor wastewater with the presence of calcium chloride (cacl2) for optimization treatment processes / Noorul Amilin Binti Saipudin - Awam, Pusat Pengajian Kejuruteraan (2017)
Semiconductor wastewater contains high organic and inorganic compounds generated from several highly complex and delicate processes. The wastewater is generally divided into three different main streams, i.e. fluoride containing, acid base and chemical mechanical polishing. In this research, a preliminary study was conducted to analyse the optimum pH range via characterization of fluoride-containing semiconductor wastewater and coagulant (CaCl2) in terms of zeta potential and hydrodynamic diameter measurements as a function of pH (pH 2-12). At each adjusted pH, the surface charge and particle size were measured using the dynamic light scattering technique. The initial pH of semiconductor wastewater suspensions were recorded at pH 5.5, +15.54 mV and 1952 d.nm for zeta potential and hydrodynamic diameter measurement respectively. The pH of point of zero charge was found at pH 7.1 with a particle size of 4500 d.nm. Characteristic analysis on CaCl2 indicated that at initial pH 5.7, zeta potential gave a negative value of -8. mV with an average particle size of 770 d.nm. The subsequent stage were optimum dosage range via interaction (aggregation and disaggregation process) between fluoride-containing semiconductor wastewater and coagulant (CaCl2) at different pH values in a systematic way by using the pHPZC of the wastewater as a point of reference. Experiment were carried out in three pH regions which are experiments set conducted were, i) pH < pHPZC, ii) pH = pHPZC and iii) pH > pHPZC. The final experiment set conducted were to measure the removal efficiency of fluoride in fluoride-containing semiconductor wastewater within the coagulant optimum dosage. When CaCl2 were added the percentage of fluoride removal for the three conditions were 13.9%, 35.5% and 29.9% respectively. These were compared to the analysis done by jar test where by the removal percentage were notes as 21.0%, 54.9% and 18.6 %. However, in experiments both analysis show that the condition pH=pHPZC gives the biggest percentages of fluoride removal. The dosage determined for the three pH region were 140 mg/L, 35 mg/L and 35 mg/L respectively.